A Study on Recovery of Metallic Values from EAF Flue Dusts - Hakan Morcali; Bora Derin; Adnan Aydin; Onuralp Yucel (The Minerals, Metals and Materials Society, 2008)
"The steelmaking industry which uses electric arc furnaces (EAF) generates approximately 250.000 tons of EAF flue dusts annually in Turkey. These flue dusts contain valuable metals such as zinc, iron and lead. For example, if these flue dusts can be treated efficiently, disposal problems certainly decreases and annually almost 40.000-75.000 tons of zinc can be recovered. In this study, powder and pellet forms of EAF flue dusts taken from a steel mill were carbothermally treated in a temperature controlled pilot scale rotary furnace via carbothermal reduction in order to investigate the reduction behavior of Zn and Pb. Temperature (900-1000 and 1100 °C) and time (0-90 minutes) were selected as reaction parameters. The chemical analysis was performed for the sample residues.IntroductionTurkey’s steel production reached to 23.3 million tons in 2006. There are three integrated steel plants of which capacities vary from 0.7 to 3 million tons per year and seventeen EAF steel plants of which capacities vary from 0.06 to 2 million tons per year [1]. When it is considered that more than 74 % of the Turkish steel production is produced by EAF method and approximately 10 - 15 kg of dust is formed per ton of steel during this process, the amount of annual generated EAF dust may be estimated at approximately 0.25 million tons. EAF dust which contains valuable metals such as zinc, lead, iron, cadmium, and chromium, is considered as hazardous waste product in steelmaking industry. If these flue dusts can be treated efficiently, not only the disposal problems certainly decrease, but also annually almost 40.000-75.000 tons of zinc can be recovered. Many studies which exist on recovering of the valuable metals from EAF dust, propose and practice many hydro-metallurgical and pyro-metallurgical treatments [2- 7]. In this study a laboratory scale work were performed to investigate reduction behavior of zinc and lead in EAF dust by carbothermal process in a rotary furnace."